Pengaruh Employee Engagemen dan Work Value Terhadap Kesiapan Berubah Pada Karyawan PT Budi Perkasa Alam - Dekalia Yulistiani; M. Rajab Lubis; Sjahril Effendy (Universitas Medan Area, 2020)
Individual readiness to change is important in the success of the organization for making changes. When employees are ready, they will be able to follow the organizational changes that occur. Employee readiness to change will have a positive impact on organizational change. There are various factors that can affect change readiness in employees including employee engagement and work value. This study aims to determine the effect of employee engagement and work value on change readiness in employees of PT. Budi Perkasa Alam. The measuring instrument used in this study is the scale of change readiness, employee engagement and work value scale. This study involved 150 employees. The results showed that partially employee engagement and work value had a positive effect on change readiness in employees with t-count value X1 (5.513) t-table (1,976) and t-count X2 (5,896) t-table (1,976). Simultaneously, employee engagement and work value variables significantly influence change readiness in PT employees. Nature Mightiness (F count = 67.230; p 0.05). Employee engagement and work value contributed to change readiness by 47.8% (R-square = 0.478). The implications of this research are expected to the management in order to maintain an understanding of the values and goals of the organization and involve employees in making organizational decisions.